Flooded cities in Low Countries fiction: Referentiality and indeterminate allegory in Renate Dorrestein's Weerwater and Roderik Six's Vloed. Issue 1 (2nd January 2020) - Ameel, Lieven; Craps, Stef
ABSTRACT: In a range of environmentally oriented international novels, future cities in the Low Countries have been flooded, with Dutch populations relocated to higher grounds or to floating cities. In contemporary Dutch and Flemish fiction, however, reflections on cities by the water are few and far between. More conspicuously, in the few literary novels that imagine cities under threat from rising water levels, the cities in question are not located on the shore but further inland, gesturing towards other meanings and symbolical repercussions rather than towards an engagement with flooding per se. This article examines two contemporary flood novels: Roderik Six's Vloed ("Flood") and Renate Dorrestein's Weerwater . We approach the floods in these novels in terms of indeterminate allegory, examining the contradictory meanings that can be attributed to the radical upheavals recounted in these narratives.